The association of cognitive function and its changes with all-cause mortality among community-dwelling older adults - Li, Shangjie; He, Xiuping; Wu, Liang; Tang, Xinming; Ouyang, Yijiang; Jing, Wenyuan; Yang, Ya; Yang, Jiacheng; Che, Kechun; Pan, Congcong; Chen, Xiaoting; Zhang, Xiaoxia; et al. (Frontiers in Aging Neuroscience, 2024)
The association of cognitive function, its changes, and all-cause mortality has not reached a consensus, and the independence of the association between changes in cognitive function and mortality remains unclear. The purpose of this study was to evaluate the longitudinal association between baseline cognitive function and cognitive changes over 1 year with subsequent all-cause mortality among the older adults aged 60 and above. increased risk of death (adjusted HR=1.79, 95% CI: 1.11-2.87), with baseline cognitive function influencing this relationship significantly (P for interaction= 0.002).Baseline cognitive impairment and rapid cognitive decline are associated with higher all-cause mortality risks in Chinese older adults. Baseline function influences the mortality impact of cognitive changes.